Mixed convection Jeffrey fluid flow over an exponentially stretching sheet with magnetohydrodynamic effect - Ahmad, Kartini; Hanouf, Zahir; Ishak, Anuar (AIP Publishing, 2016)
The steady two-dimensional MHD mixed convection boundary layer flow and heat transfer of a Jeffrey fluid over an exponentially stretched plate is investigated. The governing partial differential equations are first reduced to nonlinear ordinary differential equations, before being solved numerically using an implicit finite-difference scheme. Local similarity solutions are obtained for some embedded parameters, such as Deborah number β, mixed convection parameter λ, Prandtl number Pr and Hartmann number H, are analyzed and discussed.